Women in the Oil Industry; analysis of the views of women in a male world of work in Argentina - Muñiz Terra, Leticia (2015)
Between the 70's and the end of the 90's the productive sector of Argentina went through a profound process of decline. The companies which managed to survive had to introduce restructuring policies which were not uniform in all cases. Novick, Miravalles y Senén Gonzáles, 1997). ;The state oil company Yacimientos Petrolíferos Fiscales (YPF) was one of the firms which subsequent to it's privatization in the 90's put into practice these restructuring policies, developing an organization which subcontracted parts of it's maintenance activities and restructured the working careers of it's workers. ;In this paper we look at whether these changes at company level were accompanied by institutional and relational gender changes. In particular we ask whether these organizational changes produced a modification in the traditionally male profile of the plant workers of YPF, if stereotypes of gender were constructed in the firm, how female workers see themselves in a traditionally male oil industry and the opportunities and obstacles faced by women workers in the company